Disaster Mitigation Strategies Based on Risk Matrix and House of Risk (HoR) Phase 2 - Setiawan, Eko; Ade Fitriani, Wahyu (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
Wonogiri Regency, located in Indonesia, is an area susceptible to various types of natural disasters, such as floods, landslides, and hurricanes, which pose a significant risk to approximately 90% in this area. Therefore, this study aimed to identify the types of potential disasters in Wonogiri and propose effective strategies for disaster mitigation from 2021 to 2025. This study uses a risk matrix to quantify the risks associated with these potential disasters and utilizes House of Risk (HoR) phase 2 methodology to formulate strategies for disaster risk prevention. This comprehensive analysis has shown seven potential disasters for which nine mitigation strategies have been developed. Among these, the top three strategies, considering the effectiveness value and the degree of difficulty (EDRk) value, in order of priority, are “Increasing multi-stakeholder partnerships in disaster management” (EDRk value 176.20); “Strengthening the legal framework for disaster management” (EDRk value 167.40); and “Conducting socialization and education on disaster mitigation” (EDRk value 111.60). Implementing these strategies is expected to strengthen disaster risk reduction (DRR) in regencies, with a focus on prioritizing the most effective measures.